Who's afraid of foreign aid?: the donors' perspective - Alberto Chong; Mark Gradstein (Center for Economic Studies and ifo Institute (CESifo), 2006)
With efforts across the industrial countries to increase the amount of foreign aid mounting, it is important to understand its determinants. This paper examines the factors affecting the support for foreign aid among voters in donor countries. A simple theoretical model, which considers an endogenous determination of official and private aid flows, relates individual income to aid support through the elasticity of substitution and also suggests that government efficiency is an important factor in this regard. The empirical analysis of individual attitudes, based on the World Values Surveys, reveals that satisfaction with own government performance and individual relative income are positively related to the willingness to provide foreign aid. Furthermore, when using donor country data we find that aid is adversely affected by government inefficiency and income inequality.
Keywords: O10; H41; 330; Entwicklungshilfe; Geberländer; Schätzung; Welt